Morphogenic, structural, productive and bromatological characteristics of Braquiária in silvopastoral system under nitrogen doses - Carvalho, Zaqueu Gonçalves; Sales, Eleuza Clarete Junqueira de; Monção, Flávio Pinto; Vianna, Maria Celuta Machado; Silva, Edilane Aparecida; Queiroz, Domingos Sávio (Acta Scientiarum. Animal Sciences, 2018)
his study aimed to evaluate the effect of different doses of nitrogen fertilization on the morphogenic, structural, productive and chemical composition of Urochloa decumbens (Stapf) R. D. Webster cv. Basilisk in a silvopastoral system with eucalyptus. The experimental treatments consisted of pastures of Basilisk cultivar, fertilized with 0, 100, 200, 300 and 400 kg ha-1 year-1 of N, and intercropped with eucalyptus, clone GG 100 (Eucalyptus grandis x E. urophylla). The experimental arrangement followed a randomized block design with four replicates. The evaluated characteristics were: foliar appearance rate, phyllochron, leaf length, leaf elongation rate, leaf life span, foliar senescence rate, number of green leaves per tiller, number of senescent leaves per tiller, daily dry matter accumulation, dry matter production, crude protein, and neutral detergent fiber. In the conditions of the established silvopastoral system, nitrogen fertilization did not influence (p > 0.05) the morphogenic and structural characteristics of Basilisk cultivar, except for height (p < 0.01) and leaf: stem ratio (p = 0.02). The nitrogen fertilization of the Brachiaria grass with eucalyptus in the proposed structural arrangement does not modify (p > 0.05) the morphogenic characteristics. However, in ration to dry matter production, doses of up to 400 kg of N ha-1 are recommended.